1997
DOI: 10.1152/ajpgi.1997.273.2.g355
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diosgenin attenuates subacute intestinal inflammation associated with indomethacin in rats

Abstract: We investigated the effects of dietary diosgenin (Dio), a plant-derived sapogenin, on indomethacin (Indo)-induced intestinal inflammation and alterations in bile secretion in rats. In anesthetized rats, bile secretion, intestinal inflammation, and blood chemistry were assessed 3 days after two subcutaneous injections of Indo given 24 h apart. Dio (> 80 mg.kg-1.day-1) pretreatment significantly inhibited weight and food intake decreases and intestinal inflammation. This protective effect was confirmed by examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
1
26
0
3
Order By: Relevance
“…It has also been reported that diosgenin antagonistically suppressed the inflammatory process in various animal models (38). Diosgenin dose-dependently attenuated subacute intestinal inflammation and normalized bile secretion in indomethacin-induced intestinal inflammation in rats (38). In this study, we showed that oral administration of diosgenin and sanyaku markedly reduced the expression levels of inflammatory cytokine genes, including IL-1b, IL-6, IL-12b, and TNF-a, which were significantly elevated in the colonic mucosa of mice treated with AOM/DSS (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has also been reported that diosgenin antagonistically suppressed the inflammatory process in various animal models (38). Diosgenin dose-dependently attenuated subacute intestinal inflammation and normalized bile secretion in indomethacin-induced intestinal inflammation in rats (38). In this study, we showed that oral administration of diosgenin and sanyaku markedly reduced the expression levels of inflammatory cytokine genes, including IL-1b, IL-6, IL-12b, and TNF-a, which were significantly elevated in the colonic mucosa of mice treated with AOM/DSS (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Diosgenin inhibited the activity and expression of COX-2 in human osteosarcoma 1547 cells (33) and also abrogated basal and TNF-induced expression of COX-2 in KBM-5 cells (34), but upregulated COX-2 expression in human erythroleukemia cells (35) and noncancerous human rheumatoid arthritis synoviocytes (36). It has also been reported that diosgenin antagonistically suppressed the inflammatory process in various animal models (38). Diosgenin dose-dependently attenuated subacute intestinal inflammation and normalized bile secretion in indomethacin-induced intestinal inflammation in rats (38).…”
Section: Discussionmentioning
confidence: 93%
“…For example, diosgenin has anti-inflammatory effects in animal studies [27-29]. TNF-α, a proinflammatory cytokine, plays a pivotal role in the inflammatory processes [30], while diosgenin may have anti-inflammatory effects by reducing the responsiveness of the cells to TNF-α via ADAM10-dependent ectodomain shedding of TNFR1.…”
Section: Discussionmentioning
confidence: 99%
“…Antiproliferative effects of diosgenin are mediated through cell cycle arrest (Moalic et al, 2001;Liu et al, 2005), disruption of Ca 2 þ homeostasis (Leger et al, 2004;Liu et al, 2005), the activation of p53, release of apoptosis-inducing factor, and modulation of caspase-3 activity . It also inhibits azoxymethane-induced aberrant colon crypt foci (Raju et al, 2004) and has been shown to inhibit intestinal inflammation (Yamada et al, 1997) and modulate the activity of lipoxygenase (LOX) (Nappez et al, 1995) and cyclooxygenase-2 (COX-2) (Moalic et al, 2001). More recently, diosgenin has been shown to bind to the chemokine receptor CXCR3, which mediates inflammatory responses (Ondeykal et al, 2005).…”
Section: Introductionmentioning
confidence: 99%